Efficacy and safety of oral fluconazole in the treatment of patients with tinea corporis, cruris or pedis or cutaneous candidosis - A multicentre, open, noncomparative study - (:unkn) unknown (ADIS INTERNATIONAL LTD, 1996)
The efficacy, safety, required duration of treatment, and patient preference for oral fluconazole 150 mg/week in the treatment of 521 patients with cutaneous candidosis, tinea corporis, tinea cruris or tinea pedis were assessed in an open, multicentre, noncomparative trial. Patients received weekly doses of fluconazole 150 mg for an average of 4.65 weeks. Cultures were examined microscopically at baseline, at 2-week intervals, at study end, and at long term follow-up (4 to 6 weeks after the last dose). All adverse events were recorded and rated; patients with laboratory findings outside normal values were monitored. Forms regarding patient preference for oral or topical medication type were assessed from 19 centres at study end. Clinical evaluation demonstrated an overall success rate (cure plus improvement) of 96% at the end of therapy, and 92% overall success rate at long term follow-up. Eradication of pathogens based on culture was equally high, with 92% eradicated at the end of therapy and 89% eradicated at long term follow-up. Patient tolerability was good; only 7 patients (1.3%) discontinued therapy because of adverse events, in 2 cases because of laboratory abnormalities. These findings suggest that oral fluconazole therapy is safe. This study demonstrated that weekly oral doses of fluconazole 150 mg were effective in the treatment of tinea corporis, tinea cruris, tinea pedis and cutaneous candidosis. Furthermore, there was a high patient preference for oral fluconazole over previous topical therapy.
Keywords: 150 MG; PHARMACOKINETICS